XPharm : the comprehensive pharmacology reference - Enna, S. J.; Bylund, David B.; ScienceDirect eBooks (Amsterdam ; Boston : Elsevier, 2008)
Consisting of more than 3,700 articles, all xPharm content is commissioned by an outstanding editorial board led by past Presidents of ASPET, S.J. Enna and David B. Bylund, Ph. D. and contributed by nearly 600 experts.
Elsevier
Keywords: Pharmacology; Pharmacology; Electronic books